(untitled) (Zien Journal of Social Sciences and Humanities, 2023)
In this article you will gain main information about idioms and using them correctly. In addition, you may find the number of replies for questions like what are idioms, what are the types of idioms, how are idioms structured and why are idioms used? You will be given information to increase IELTS score by using idioms, give tips for using them in exact place and examples of idioms. Finally, given interesting exercise in order to understand the meaning and learn utilizing them correctly.